2024
DOI: 10.1027/1015-5759/a000733
|View full text |Cite
|
Sign up to set email alerts
|

Receptivity to Instructional Feedback

Abstract: Abstract. The purpose of this study was to report validity evidence for the instrument intended to measure receptivity to instructional feedback in a sample of secondary school students from Singapore ( N = 314). We tested a nested hierarchy of hypotheses for addressing the cross-group (i.e., gender) invariance and compared means on the receptivity to feedback subscales between gender groups. We also examined whether receptivity to feedback predicted student grades. The four-factor hypothesized model comprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Moreover, Lipnevich and Lopera-Oquendo (2022) found that the subscales of experiential attitudes and cognitive and behavioral engagement positively predicted student grades. Thus, the convergent validity of the scale was demonstrated for the prediction of important educational outcomes.…”
Section: Receptivity To Instructional Feedback (Rif)mentioning
confidence: 97%
See 4 more Smart Citations
“…Moreover, Lipnevich and Lopera-Oquendo (2022) found that the subscales of experiential attitudes and cognitive and behavioral engagement positively predicted student grades. Thus, the convergent validity of the scale was demonstrated for the prediction of important educational outcomes.…”
Section: Receptivity To Instructional Feedback (Rif)mentioning
confidence: 97%
“…RIF is a construct that originated in personality psychology and is described as trait-like feedback receptivity (Lipnevich & Lopera-Oquendo, 2022). RIF rests on the assumption that individuals may have varying degrees of willingness or readiness to accept feedback (Lipnevich et al, 2016).…”
Section: Receptivity To Instructional Feedback (Rif)mentioning
confidence: 99%
See 3 more Smart Citations